A study of the relationship between monocotyledonous plant anatomy and water - Jones, Dylan (2023)
Plant anatomy is known to significantly affect many aspects of organ function, as well as the metabolic cost of maintenance and production of plant tissues. Of particular importance is the role of anatomy in plants ability to uptake, transport and utilize water efficiently. Despite this, it remains an unexploited target in crop improvement. The anatomy of duckweeds (aquatic plants with an evolutionary trajectory towards rootlessness) was investigated. Significant root anatomical reduction (particularly in the vasculature) was accompanied by a significant reduction in the functions of the root tested, concluding that duckweed roots have lost their ancestral function and can be considered vestigial. In larger plants it can be more technically challenging to investigate anatomical traits, particularly in a high throughput manner. This requires the development of new methods. Using the novel method of Laser Ablation Tomography (LAT), anatomical phenotyping pipelines were developed and tested on brachypodium, maize, gamagrass, and pearl millet. This included the production of deep-learned fully automatic root image analysis software. These methods were then employed in an investigation of water stress tolerance in pearl millet lines from an association panel. This showed that there was significant root and leaf anatomical variation in this collection, and that anatomical traits were affected by water stress. Further analysis showed that several root anatomical traits were highly correlated with agronomic traits, and genomic analysis was able to identify several single nucleotide polymorphisms associated with these anatomical traits.